2009
DOI: 10.1097/qad.0b013e32832b51be
|View full text |Cite
|
Sign up to set email alerts
|

Inverse association of repressor growth factor independent-1 with CD8 T cell interleukin (IL)-7 receptor α expression and limited signal transducers and activators of transcription signaling in response to IL-7 among γ-chain cytokines in HIV patients

Abstract: IL-7 stimulation failed to activate STAT5 in a substantial proportion of patient CD8 T cells. This correlated with reduced IL-7Ralpha mRNA and surface protein expression. Interestingly, IL-7Ralpha(low) cells appeared to be fully capable of recruiting the STAT pathway in response to IL-2, IL-4, IL-10, and IL-15. mRNA expression suggested a potential role for growth factor independent (Gfi)-1 as an IL-7Ralpha transcriptional repressor, but not that of other transcriptional regulators studied, including Gfi-1B an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 44 publications
2
9
0
Order By: Relevance
“…The regulation of CD127 by HIV may play a role in disease pathogenesis since the expression of CD127 has been correlated with measures of disease progression (decreased CD4 count, increased viral load, increased immune activation) [24,25]. In addition to decreased CD127 expression on T-cells, we and others have also shown that CD127 signalling is impaired in HIV infection [26-28]. Given the importance of the role of IL-7 in HIV pathogenesis and the current development of IL-7 as a therapeutic agent for HIV infection and other conditions, understanding the mechanism by which HIV impairs IL-7 activity within the thymus is of the greatest importance.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The regulation of CD127 by HIV may play a role in disease pathogenesis since the expression of CD127 has been correlated with measures of disease progression (decreased CD4 count, increased viral load, increased immune activation) [24,25]. In addition to decreased CD127 expression on T-cells, we and others have also shown that CD127 signalling is impaired in HIV infection [26-28]. Given the importance of the role of IL-7 in HIV pathogenesis and the current development of IL-7 as a therapeutic agent for HIV infection and other conditions, understanding the mechanism by which HIV impairs IL-7 activity within the thymus is of the greatest importance.…”
Section: Resultsmentioning
confidence: 97%
“…While in vitro HIV infection did not affect surface CD127 expression on thymocytes, it remains possible that in vitro HIV infection is associated with altered IL-7 signalling as has been reported in CD8 + T-cells from HIV-infected individuals [26-28]. This was, therefore, evaluated by measuring IL-7 responsiveness of thymocytes following HIV infection.…”
Section: Resultsmentioning
confidence: 99%
“…ϩ T-cell subset of viremic patients with high levels of chronic immune activation, which may account for the perturbed IL-7 responses observed in this subset (11,22,41,49,54,60). However, it should be noted that decreased CD127 expression may be compensated for by increased ␥c expression and that the net effect of these changes on IL-7 binding capacity has not been investigated so far.…”
Section: Interleukin 7 (Il-7) Plays a Central Role In Controlling Cd4mentioning
confidence: 99%
“…It is plausible that diminished IL-7 receptor expression (CD127) is a key determinant of reduced IL-7 responsiveness in HIV disease. In support of this possibility, some studies have found a tight correlation between IL-7-induced P-STAT5 signaling and CD127 expression, particularly among CD8 cells [11]. Nonetheless, isolated CD8+CD127+ cells from HIV+ donors have defects in P-STAT5 signaling [13].…”
Section: Introductionmentioning
confidence: 96%
“…The IL-7/IL-7 receptor axis is perturbed in HIV disease such that serum levels of IL-7 cytokine are increased [4] while T cell expression of IL-7 receptor is diminished [5], [6], [7], [8], [9], [10]. T cells from HIV-infected persons also tend to display poor intracellular signaling responses to IL-7 stimulation, particularly as measured by phosphorylation of STAT-5 [5], [11], [12], [13]. These perturbations in IL-7 responsiveness could contribute to HIV pathogenesis and adversely affect T cell reconstitution during administration of anti-retroviral therapy.…”
Section: Introductionmentioning
confidence: 99%